2019
DOI: 10.1111/1759-7714.13285
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐148b suppressed non‐small cell lung cancer progression via inhibiting ALCAM through the NF‐κB signaling pathway

Abstract: Background: Non-small cell lung cancer (NSCLC) is the leading cause of cancer mortality worldwide. MiRNAs are recognized as important molecules in cancer biology. The aim of the study was to identify a novel biomarker miR-148b and its mechanism in the modulation of NSCLC progression. Methods: The expressional level of miR-148b was analyzed by RT-PCR. The effect of miR-4317 on proliferation was evaluated through 3-(4,5-Dimethyl-2-thiazolyl)-2,5-diphenyl-2Htetrazolium bromide (MTT) assay. The effect of miR-148b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…These inconsistencies may be due to the differences between sample origins and the tumor clinicopathological characteristics (33); therefore, further research should be conducted in various human cancer types to determine the effect of miR-590-5p. The role of miRNA molecules in lung cancer, such as miR-148b, miR-590-3p and miR-455-5p, has been investigated in previous studies (39)(40)(41). miR-590 has been proposed to act as an oncogene or as a tumor suppressor gene depending on the target (42).…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistencies may be due to the differences between sample origins and the tumor clinicopathological characteristics (33); therefore, further research should be conducted in various human cancer types to determine the effect of miR-590-5p. The role of miRNA molecules in lung cancer, such as miR-148b, miR-590-3p and miR-455-5p, has been investigated in previous studies (39)(40)(41). miR-590 has been proposed to act as an oncogene or as a tumor suppressor gene depending on the target (42).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that miR-148b plays an important role in cancer dynamics, including melanoma. In non-small-cell lung cancer, miR-148b suppresses tumor growth and metastasis by regulating the NF- κ B and MAPK/JNK pathways [ 28 , 29 ]. Leong et al reported that miR-148a/b-3p targets an isoform of RAS-like protein (RALBP1) and thus functions as a tumor suppressor in oral squamous cell carcinomas [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, attempts have been conducted in improving knowledge toward genetic factors responsible for the development and progression of these thoracic cancers. MicroRNAs (miRNAs), as non-coding and short RNA molecules, are considered as potential diagnostic, therapeutic, and prognostic factors for breast and lung cancers [ 19 , 20 ]. There are two major types including tumor-suppressor and tumor-promoting miRNAs whose roles in the development of breast and lung cancers have been elucidated [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%